Ոստիկանի անձնային առանձնահատկությունների և գործունեության անհամատեղելի գործոնների հարաբերակցությունը - Ն. Մ. Նազարյան (ՀՀ ԳԱԱ հրատ.)
Особенности профессиональной деятельности влияют на формирование и проявление личностных характеристик полицейского как субъекта деятельности. Peculiarities of professional activity influence formation and demonstration of police officer’s personal characteristics as a subject of activity.
Keywords: B Philosophy; Psychology; Religion; Psychology